TRANSLATORS AS MEDIATOR: CULTURAL NEGOTIATION IN TRANSLATING ENGLISH LITERARY TEXT INTO INDONESIAN - Nadia Khumairo Ma'shumah; Aulia Addinillah Arum; Arif Nur Syamsi (Universitas Islam Sumatera Utara (UISU), 2021)
This study explores the translation of cultural-specific terms in the literary text as the translation process connects cultural differences between the source and target languages. Using Eco's notion of